Application of α-Aminoalkyl Radicals as Reaction Activators - Su, Yong-Liang; Doyle, Michael P. (Synthesis, 2021)
α-Aminoalkyl radicals are easily accessible through multiple pathways from various precursors. Apart from their utilization as nitrogen-containing building blocks, they have recently been used as halogen atom abstraction reagents or single-electron reductants to transform organic halides or sulfonium salts into their corresponding highly reactive radical species. Benefiting from the richness of various halides and the diverse reactivity of radical intermediates, new transformations of halides and sulfonium salts have been developed. This short review summarizes this emerging chemistry that uses α-aminoalkyl radicals as the reaction activators.1 Introduction2 Activation of Halides as Halogen-Atom Transfer Agents2.1 Addition to Unsaturated Bonds2.1.1 Addition to C=C Bonds2.1.2 Addition to C=O Bonds2.2 Substitution Reactions2.2.1 Deuteration2.2.2 Olefination2.2.3 Allylation2.2.4 Aromatic Substitution2.2.5 Amination3 Activation of Sulfonium Salts as Single-Electron Reductants4 Conclusion and Outlook
Keywords: α-aminoalkyl radicals; halides; halogen-atom transfer; hydrogen-atom transfer; radical addition; radical substitution; sulfonium salts